Averus Jakarta Vocational Administration Application Using Client-Server Architecture and Model-View-Controller - Yulianti; Normalisa (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
SMK Averus Jakarta yang terletak di Pondok Pinang, Jakarta Selatan merupakan salah satu institusi pendidikan yang belum menggunakan teknologi informasi karena data administrasinya sebagian dicatat dan diolah secara manual, walaupun sudah ada yang dicatat dan diolah menggunakan Microsoft Excel. Hal ini menyebabkan beberapa masalah seperti, banyak terjadi duplikasi data dan pembuatan laporan-laporan dari data-data administrasi cenderung lambat. Salah satu solusi untuk menyelesaikan permasalahan tersebut yaitu pembuatan aplikasi administrasi sekolah menggunakan arsitektur Client Server dan Model View Controller (MVC). Arsitektur Client-Server membagi aplikasi dalam dua bagian yaitu server yang berhubungan dengan pengelolaan basis data dan client yang berhubungan dengan antarmuka user. Sedangkan arsitektur MVC dapat mempermudah pengembangan aplikasi sesuai dengan kebutuhan di masa depan dan dapat mengurangi jumlah source code. Setelah pembangunan aplikasi selesai, disimpulkan bahwa aplikasi ini dapat mengurangi duplikasi data, memperbaiki organisasi data/dokumen, mempercepat pembuatan laporan yang diperlukan, dan meningkatkan efisiensi dan efektifitas pengembangan aplikasi. Averus Jakarta Vocational Administration Application Using Client-Server Architecture and Model-View-Controller Abstract: Averus Jakarta Vocational School, located in Pondok Pinang, South Jakarta is one of the educational institutions that has not used information technology because its administrative data is partially recorded and processed manually, although some have been recorded and processed using Microsoft Excel. This causes several problems such as, a lot of data duplication and making reports from administrative data tend to be slow. One solution to solve this problem is the creation of a school administration application using Client Server architecture and Model View Controller (MVC). Client-Server Architecture divides the application into two parts, namely the server that is associated with database management and the client that is related to the user interface. While the MVC architecture can facilitate the development of applications according to future needs and can reduce the amount of source code. After the application development is completed, it is concluded that this application can reduce data duplication, improve data / document organization, speed up the reporting required, and improve the efficiency and effectiveness of application development. Keywords: Client-Server, Model-View-Controller, School Administration.